EMPOWERING RESEARCH, DEVELOPMENT AND COMMERCIALISATION THROUGH SUSTAINABLE DEVELOPMENT GOALS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 7 December 2016 One way of describing sustainability is that, it is about developing innovation to create wealth using two pathways, which are entrepreneurial innovation or social innovation.